(untitled) (Journal of the College of Basic Education, 2022)
1 - the level of spatial capacity of students in the fourth grade primary. 2 - the level of visual thinking among students in the fourth grade of primary. 3 - Relation of spatial ability to visual thinking among fourth graders. Two tests were conducted: the first was a spatial capacity test, the number of paragraphs was 30, and its stability was calculated by using the Kjoder Richardson-20 equation where it reached 0.87. The other was a visual reflection test. The number of paragraphs was 30. (0.80) The two tests were applied to the research sample of (100) students and students of the fourth grade primary school. To achieve the research objectives, the following statistical methods were used: T-test and Pearson correlation coefficient. 1 - The students of the research sample possess spatial capacity and good level. 2 - Students in the research sample do not have visual thinking. 3 - There is a direct relationship between spatial capacity and visual thinking. In the light of these results, a number of recommendations and suggestions were made for subsequent research and studies.